Infection and immunity on a chip: a compartmentalised microfluidic platform to monitor immune cell behaviour in real time1. Issue 6 (21st March 2015) - Gopalakrishnan, N.; Hannam, R.; Casoni, G. P.; Barriet, D.; Ribe, J. M.; Haug, M.; Halaas, Ø.
<x xml:space="preserve">Abstract</x> Immunity on a chip: modeling and designing immune reactions in vitro to study immune responses on a chip as well as unraveling physiological processes under a microscope.